Hell heaven in Tipitaka: นรก-สวรรค์ ในพระไตรปิฎก - Dhammavuddho, Phrapalat Apisit; Thitapanyo, PhramahaMit (Journal of Graduate MCU KhonKaen Campus, 2022)
The book on Hell-Heaven in the Tripitaka written by Somdej Phra Buddhakosachan (PA Payutto) Hell, Heaven in Buddhism Heaven is not the destination of Buddhism. But Buddhism says there is something higher than that. What is more important than heaven is nirvana when we practice Dharma in Buddhism. If we practice under the principles, we were told not for heaven, but for nirvana, hell, and heaven as it is known or talked about. It is something that is gained or experienced after death. Other religions generally say this. When we die, we go to hell or heaven. The purpose of those religions is therefore a matter of life ahead. But the aim of Buddhism is attainable in this life.